Diagnosis and control of Equine Infectious Anemia in a horse farm located in Buenos Aires province, Argentina - Vissani, Maria Aldana; Reynal O'Connor, J.; Olguin Perglione, Cecilia; Traverso, S.; Gutierrez, G.; Alvarez, Irene; Barrandeguy, Maria Edith (2017)
Inst.de Virología